Spanning the Strait : studies in unity in the western Mediterranean - Liang, Yuen-Gen, 1974-; Balbale, Abigail Krasner; Devereux, Andrew; Gomez-Rivas, Camillo (Medieval encounters, 2013)
Spanning the Straight: Studies in Unity in the Western Mediterranean brings together a multidisciplinary collection of essays that examines the deep connections that bound together the Iberian Peninsula and the Maghrib in the medieval and early modern periods.